Responsabilidad social y su incidencia en la imagen institucional de la I.E. Ricardo Palma Soriano – Distrito de Sanagoran 2020 - Layza Alva, Mailin Betzabé (2021)
The present investigation was carried out with the Sanagoran District as the geographical setting, specifically in the I.E. Ricardo Palma Soriano, his main objective being to evaluate internal social responsibility and its influence on the Institutional Image of the I.E. Ricardo Palma Soriano, from the District of Sanagoran 2020, Province of Sánchez Carrión, the research carried out according to its scope is descriptive, not experimental, the Inductive-Deductive Method was used, the Hypothetical-Deductive Method, it was used as a collection technique of data, to the survey questionnaire, to validate the reliability of said data collection instrument, the Cronbach's Alpha method was applied, obtaining an index of 0.806 for the total survey, for the Social Responsibility variable an index equal to 0.802 and a index of 0.823 for the variable Institutional Image; We worked with two populations, one for each variable, in the case of the Social Responsibility variable, we did not work with a sample, it was done with the population by size, for the variable Institutional image we worked with a sample, which in our case is equivalent to 108 parents, the data collection instrument was applied to these samples, and with the information obtained it was possible to meet the proposed objectives, test the hypothesis and determine as the main result that the study variables are related positively, with a correlation coefficient equal to 0.450 that shows this relationship.